Innovative Approaches to Radiation Treatment for Mycosis Fungoides in the Setting of Collagen Vascular Disease - Stephanie A. Terezakis; George C. Bohle; Ying-Chun Lo; Sean L. Berry; Joachim Yahalom (Case Reports in Oncological Medicine, 2015)
Patients with connective tissue disorders are clinically challenging for radiation oncologists as these patients may be at increased risk for radiation-related skin toxicity. A clinical dilemma presents itself in a patient with lupus who presents with confluent skin lesions from mycosis fungoides requiring radiotherapy. In this report, we discuss an innovative technique used to develop an immobilization device that also effectively functioned as a uniform bolus with distinct dosimetric advantages to the use of a facial moulage.